Predictive values of Alvarado score, serum C-reactive protein, and white blood cell count in the diagnosis of acute appendicitis: a prospective study - Ademola Olusegun Talabi; Tewogbade Adeoye Adedeji; Oludayo Adedapo Sowande; Olusanya Adejuyigbe (SpringerOpen, 2021)
Abstract Background The diagnosis of acute appendicitis in children is quite challenging as the rate of negative appendectomy varies between 15 and 57%. Increased utilization of imaging diagnostic facilities in advanced countries seems to have reduced the incidence of operating on normal appendix to a single digit. In low- and middle-income countries, the incidence remains unacceptably high (double digits). Inflammatory markers and scoring systems may be a suitable adjunct to increase diagnostic yield in most third world countries. Thus, the aim of this study was to evaluate the diagnostic value of Alvarado score, white blood cell count, and serum C-reactive protein in children with acute appendicitis. Results The ages of patients ranged between 4 and 15 years with a mean of 11.2 ± 2.8 years. The male to female ratio was 1.4 to 1.0. Nineteen percent of patients had negative appendiceal findings on histological examination. The sensitivity and specificity of Alvarado score, C-reactive protein estimation, total white blood cell count in diagnosing acute appendicitis were 86.4% and 63.2%, 98.8% and 36.8%, and 51.9% and 89.5% respectively. Alvarado score has the highest area under ROC curve analysis 0.824, 95% CI of 0.724 to 0.924 compared with CRP, 0.769. 95% CI of = 0.647 to 0.891 and WBC count, 0.765, 95% CI of 0.643 to 0.887. Both CRP and WBC count showed higher discriminatory values between complicated and uncomplicated appendicitis, p < 0.001. Conclusion Alvarado score outperformed other tests in setting the diagnosis of acute appendicitis. However, none of the tests can be relied on wholly for operative decision. Clinical judgement remains the bedrock for diagnosis and operative management.